Enhancing of SNR and Optical Power Distribution in Indoor Visible Light Communications Systems - Abdelrahman, Shereen Eltayib; Abdulwahab, mortada mohammed (Journal of Telecommunication, Electronic and Computer Engineering (JTEC), 2019)
There are many difficulties that limit the applications of indoor visible light communication systems VLC such as nonuniformed power distribution, high signal to noise ratio (SNR). This paper proposed mathematical models for diffuse channel configuration and light of sight (LOS) channel configuration. All models in this paper assumed to have an arrangement of four LEDs on the room ceiling along the orthogonal axes. The paper investigates the indoor light power distribution and SNR in each layout model of LEDS . The results selected the optimized deployment in a room of 8m length, 8m width and 3 m height. The best deployment of the LOS configurations where selected to guarantee uniform received optical power distribution and acceptable SNR value. The diffuse channel configuration shows high interference rate when the sources located closed to walls.